The Libyan NTC Law No.38 2012: a disguised amnesty - Hamed Hashemi Sougheh; Rohaida Nordin (Penerbit Universiti Kebangsaan Malaysia, 2019)
The armed conflict of Libya occurred in 2011 and the authoritarian government of Ghaddafi felt down. During the conflict serious violations of human rights and humanitarian rights law (IHL) occurred and both sides committed serious crimes included of willfull killings, rape, looting, torture and aarbitrary arrests. After the fall of Ghoddafi, a transitional government came to power in Libya that was known as the National Transitional Government of Libya (NTC). The Libyan NTC adopted amnesty laws and considered it as part of the transition of power from the previous government to the new one. This amnesty law was criticized by human rights organizations and human rights activists. In this article after providing a brief introduction to amnesty and introducing various types of it and contemplating on transitional justice, the NTC amnesty law will be examined.